2018
DOI: 10.1128/msphere.00462-17
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Dependent Regulation of Methylotrophy in Methylobacterium aquaticum Strain 22A

Abstract: Lanthanides have been considered unimportant for biological processes. In methylotrophic bacteria, however, a methanol dehydrogenase (MDH) encoded by xoxF was recently found to be lanthanide dependent, while the classic-type mxaFI is calcium dependent. XoxF-type MDHs are more widespread in diverse bacterial genera, suggesting their importance for methylotrophy. Methylobacterium species, representative methylotrophic and predominating alphaproteobacteria in the phyllosphere, contain both types and regulate thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 53 publications
16
86
0
Order By: Relevance
“…While in the absence of Ln 3+ the oxidation of methanol in methylotrophs is driven by Ca 2+ -dependent PQQ-MDHs (MxaF-type), the presence of low amounts of REE ions is usually sufficient to trigger a transcriptional switch to the XoxF-type of PQQ-MDHs. This inverse regulation, called the REE switch, has been described for many methano- and/or methylotrophic organisms (Farhan Ul Haque et al, 2015; Chu and Lidstrom, 2016; Vu et al, 2016; Gu and Semrau, 2017; Masuda et al, 2018; Zheng et al, 2018). From the growing number of studies, it has become apparent that the molecular mechanism underlying this switch for PQQ-MDHs is complex and can substantially differ among species.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…While in the absence of Ln 3+ the oxidation of methanol in methylotrophs is driven by Ca 2+ -dependent PQQ-MDHs (MxaF-type), the presence of low amounts of REE ions is usually sufficient to trigger a transcriptional switch to the XoxF-type of PQQ-MDHs. This inverse regulation, called the REE switch, has been described for many methano- and/or methylotrophic organisms (Farhan Ul Haque et al, 2015; Chu and Lidstrom, 2016; Vu et al, 2016; Gu and Semrau, 2017; Masuda et al, 2018; Zheng et al, 2018). From the growing number of studies, it has become apparent that the molecular mechanism underlying this switch for PQQ-MDHs is complex and can substantially differ among species.…”
Section: Introductionmentioning
confidence: 89%
“…Notably, due to their low solubility in most natural environments, REEs have long been considered to have no biological function (Sarkar, 2002). However, the discovery of the wide-spread occurrence of the REE-dependent XoxF-type of PQQ-dependent methanol dehydrogenases (PQQ-MDHs), together with the more recent description of Ln 3+ -dependent ethanol dehydrogenases, has highlighted the important role of REEs for many bacterial species in various environmental compartments (Fitriyanto et al ., 2011a; Fushimi, et al, 2011; Pol et al, 2014; Taubert et al, 2015; Chu and Lidstrom, 2016; Good et al, 2016; Vekeman et al, 2016; Shiller et al, 2017; Wehrmann et al, 2017; Lv et al, 2018; Masuda et al, 2018). While in the absence of Ln 3+ the oxidation of methanol in methylotrophs is driven by Ca 2+ -dependent PQQ-MDHs (MxaF-type), the presence of low amounts of REE ions is usually sufficient to trigger a transcriptional switch to the XoxF-type of PQQ-MDHs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of methanotrophs, difficulties in culturing the Verrucomicrobial microbes isolated from Italian mud-pots were solved by the addition of various REEs including La(III), Ce(III), Pr(III), and Nd(III) [12]. These lanthanides transcriptionally regulate the expression of MxaF and XoxF in a number of methylotrophs and methanotrophs [1316]. For Methylomicrobium ( Mm .)…”
Section: Introductionmentioning
confidence: 99%
“…Although being among the most ubiquitous metals in the earth’s crust, REEs were long considered to be of no biological relevance due to their low solubility under environmental conditions (14). Indeed, the only known and characterized REE-dependent enzymes thus far belong to the family of PQQ-ADHs of methano- and methylotrophic bacteria as well as the non-methylotrophic organism P. putida KT2440 (12, 1520). A characteristic aspartic acid that is additionally present in the metal coordination sphere of these enzymes is associated with Ln 3+ -binding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their functional role as metal cofactor, several studies have recently investigated the effect of REEs on cellular physiology in different methano- and methylotrophic organisms (20, 27–32). Some of these studies found different physiological traits to be influenced in response to Ln 3+ -availability including changes in metabolite cross-feeding, growth rates and-yields, or biofilm formation.…”
Section: Introductionmentioning
confidence: 99%